Change of Retinal Vessels in Different Sectors of the Parapapillary Area in Primary Open-Angle Glaucoma - Cheng, Jingyi; Zhao, Hongmei; Jiang, Chunhui; Kong, Xiangmei; Sun, Xinghuai (Frontiers in Medicine, 2021)
Purpose: To investigate the changes in the retinal vessels (RVs) in different sectors in patients with primary open-angle glaucoma (POAG), and their possible correlations with retinal nerve fiber layer thickness (RNFLT) and visual-field defects in the temporal parapapillary region. Methods: The RV diameters, RNFLTs, and visual-field parameters were measured. The temporal parapapillary region was divided into the temporal (T, 315°–45°), temporal superior (TS, 45°–90°), and temporal inferior sectors (TI, 270°–315°). The changes in the RV diameters in each sector were determined, and their relationships with RNFLT, the mean deviation (MD), and visual field sensitivity (VFS) were examined. Results: Fifty POAG patients (50 eyes) and 50 healthy subjects (50 eyes) were included. Compared with the healthy subjects, the POAG group had a significantly smaller accumulated parapapillary RV diameter (P < 0.001), which was positively correlated with the MD and RNFLT. When the different temporal sectors were examined, the accumulated RV diameters were significantly smaller in the POAG group than in the healthy controls in the TI and T sectors, but not in the TS sector. The accumulated diameters in the TI and T sectors were correlated with the corresponding RNFLTs (all P < 0.05), but only the accumulated diameter in the TI sector was correlated with the VFS. Conclusions: In POAG, the changes in the RVs differed between different temporal sectors, with the most prominent changes occurring in the TI and T sectors.